2005
DOI: 10.1007/s11099-005-0083-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of paracrystalline structures from transgenic Pssu-ipt tobacco

Abstract: Distinct crystalloids were found in chloroplasts of transgenic Pssu-ipt tobacco (Nicotiana tabacum L. cv. Petit Havana SR1) overproducing endogenous cytokinins. They were present both in rooted (T) and grafted (TC) transgenic plants contrary to control tobacco (C). The fractions enriched by crystalloids were isolated from chloroplasts using a continuous or a discontinuous Percoll gradient. Chlorophyll (Chl) fluorescence emission spectra at 77 K indicated the presence of aggregates of light-harvesting complex p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…We can only speculate on the fact that, if any imbalance in LHC apoprotein and Chl a and b synthesis caused by CKs exists, then it could probably be the mechanism used to balance the optimal functioning of the photosynthetic apparatus again. This is supported by the fact that those aggregates are not connected to photosystems and photosynthetic complexes in normal thylakoid membranes, which was proved by spectrofluorometric analysis (Synkova´et al 2005).…”
Section: Ultrastructurementioning
confidence: 88%
“…We can only speculate on the fact that, if any imbalance in LHC apoprotein and Chl a and b synthesis caused by CKs exists, then it could probably be the mechanism used to balance the optimal functioning of the photosynthetic apparatus again. This is supported by the fact that those aggregates are not connected to photosystems and photosynthetic complexes in normal thylakoid membranes, which was proved by spectrofluorometric analysis (Synkova´et al 2005).…”
Section: Ultrastructurementioning
confidence: 88%
“…non-Q Breducing or silent reaction centres), which may act as dissipative sinks, thereby decreasing F 0 (Öquist et al 1992). In our previous study, Chl fluorescence emission spectra at 77 K indicated the presence of aggregates of light-harvesting complex proteins (LHCII) that were not connected to reaction centres of PSII in Pssu-ipt transgenic tobacco (Synková et al 2005). Lower F m is again an indication of the energy dissipation via nonphotochemical pathways.…”
Section: Fast Chl a Fluorescence Induction Kineticsmentioning
confidence: 90%